Political Instability and Hiv/Aids Response in The South West and North West Region of Cameroon: A Qualitative Study - Julius, Mekolle, Enongene; Edouard, Tshimwanga, Katayi; Ongeh, Niba, Juste; Agbornkwai, Agbor, Nyenty; Amadeus, Omeichu, Agwenam; Esa, Ismaela; Mekolle, Keshia, Ebude; Forbinake, Ndung, Ako; Nkfusai, Claude, Ngwayu; Atanga, Pascal, Nji (My University, 2023)
Background: Politically motivated violence and insecurity continue to be a major threat to HIV progress and a significant contributor to health inequality. Despite a decreasing HIV/AIDS disease burden, the Republic of Cameroon in West Africa is experiencing ongoing political instability in her North and South West Regions. Our study used qualitative methods to better understand key frontline health care providers' (fHCP) perceptions of the effects of political instability on HIV/AIDS response gains in Cameroon since 2018, as well as lessons learned for overcoming them. Methods: Between July and August 2022, semi-structured, in-depth key informant interviews involving 10 purposively selected participants were conducted in the two regions. Interviews were recorded and transcribed verbatim, coded thematically, and analyzed manually. Results: Six overarching themes emerged from the transcribed key informant interviews. They were as follows: (1) Challenge with access to and availability of health care services (HIV care, commodity supply chain) in the smaller communities; (2) Impact on continuity of treatment; (3) Increased risk of new HIV infections. (4) The socioeconomic impact of the crisis on the quality of life; (5) The impact of the crisis on fHCPs' physical and mental health and the health system'; and (6) Coping mechanisms Conclusions: Frontline healthcare workers have acknowledged the significant impact the current political instability has had in hindering the development and advancement of a successful local response to HIV/AIDS in the two impacted regions of Cameroon. Coordinated efforts must be made to strengthen the health sector in areas such as HIV healthcare decentralization, supply chain, and protecting frontline healthcare workers from political quagmires in order to lessen the impact of the nation's socio-political crisis on the HIV/AIDS response and, more generally, on the entire health sector.
Keywords: Cameroon; Global health; HIV/AIDS; Political instability; Qualitative health research